"O Youth and Beauty:" Children's Looks and Children's Cognitive Development - Daniel S. Hamermesh; Rachel A. Gordon; Robert Crosnoe (Institute of Labor Economics (IZA), 2019)
We use data from the 11 waves of the U.S. Study of Early Child Care and Youth Development 1991-2005, following children from ages 6 months through 15 years. Observers rated videos of them, obtaining measures of looks at each age. Given their family income, parents' education, race/ethnicity and gender, being better-looking raised subsequent changes in measurements of objective learning outcomes. The gains imply a long-run impact on cognitive achievement of about 0.04 standard deviations per standard deviation of differences in looks. Similar estimates on changes in reading and arithmetic scores at ages 7, 11 and 16 in the U.K. National Child Development Survey 1958 cohort show larger effects. The extra gains persist when instrumenting children's looks by their mother's, and do not work through teachers' differential treatment of better-looking children, any relation between looks and a child's behavior, his/her victimization by bullies or self-confidence. Results from both data sets show that a substantial part of the economic returns to beauty result indirectly from its effects on educational attainment. A person whose looks are one standard deviation above average attains 0.4 years more schooling than an otherwise identical average-looking individual.
Keywords: J71; I26; I24; 330; beauty; learning; education